Post‐infection pulmonary sequelae after COVID‐19 among patients with lung transplantation. Issue 6 (17th October 2021) - Mahan, Luke D.; Lill, Isaac; Halverson, Quinn; Mohanka, Manish R.; Lawrence, Adrian; Joerns, John; Bollineni, Srinivas; Kaza, Vaidehi; La Hoz, Ricardo M.; Zhang, Song; Kershaw, Corey D.; Terada, Lance S.; et al.
Abstract: Background: There is limited data on outcomes among lung transplant (LT) patients who survive Coronavirus disease 2019 (COVID‐19). Methods: Any single or bilateral LT patients who tested positive for SARS‐CoV‐2 between March 1, 2020, to February 15, 2021 ( n = 54) and survived the acute illness were included (final n = 44). Each patient completed at least 3 months of follow‐up (median: 4.5; range 3–12 months) after their index hospitalization for COVID‐19. The primary endpoint was a significant loss of lung functions (defined as > 10% decline in forced vital capacity (FVC) or forced expiratory volume in 1 s (FEV1 ) on two spirometries, at least 3 weeks apart compared to the pre‐infection baseline). Results: A majority of the COVID‐19 survivors had persistent parenchymal opacities ( n = 29, 65.9%) on post‐infection CT chest. Patients had significantly impaired functional status, with the majority reporting residual disabilities (Karnofsky performance scale score of 70% or worse; n = 32, 72.7%). A significant loss of lung function was observed among 18 patients (40.9%). Three patients met the criteria for new chronic lung allograft dysfunction (CLAD) following COVID‐19 (5.6%), with all three demonstrating restrictive allograft syndrome phenotype. An absolute lymphocyte count < 0.6 × 10 3 /dl and ferritin > 150 ng/ml at the time of hospital discharge was independently associated with significant lung function loss. Conclusions: A significant proportion of COVID‐19 survivors suffer persistent allograft injury. Low absolute lymphocyte counts (ALC) and elevated ferritin levels at the conclusion of the hospital course may provide useful prognostic information and form the basis of a customized strategy for ongoing monitoring and management of allograft dysfunction. Tweet: Twitter handle: @AmitBangaMD Lung transplant patients who survive COVID‐19 suffer significant morbidity with persistent pulmonary opacities, loss of lung functions, and functional deficits. Residual elevation of the inflammatory markers is predictive.